Complete mesocolic excision for colon cancer is technically challenging but the most oncological appealing - Negoi, Ionut; Beuran, Mircea; Hostiuc, Sorin; Sartelli, Massimo; Coccolini, Federico; Vartic, Mihaela; Pinkney, Thomas (Translational Gastroenterology and Hepatology; Vol 3 (October 2018): Translational Gastroenterology and Hepatology, 2018)
We read with really great interest the paper published by Gao et al. in Annals of Surgery (1). The authors presented the 3-year interim results of the Efficacy Study of Complete Mesocolic Excision, which is a prospective, non-randomized study with a planned duration of 5 years, started in 2012 (1). The main objective of this study is to evaluate the safety and effectiveness of complete mesocolic excision for colon cancer treatment. Gao et al. included 220 and 110 patients in the CME and conventional surgery groups, respectively. An important strength of the current study is the evaluation of the specimens by blinded third-party experts (1).